Species relationships among wild and cultivated Abelmoschus Medik., (Malvaceae) species as reveled by molecular markers - Patil Pravin; Sutar Shrikant; Bhat Kangila Venkataraman (International Journal of Life Sciences, 2018)
The genus Abelmoschus is represented by more than 10 species which shows wide distribution over the diverse agro−climatic conditions of Indian subcontinent. In the present study, total 60 accessions of eleven Abelmoschus species were subjected to estimate genetic diversity and species relationships. Out of 200 primers 21 primers was found to be considerable for cluster analysis. All 21 primers produced total 321 amplicons with ranges from nine (OPA-5) to nineteen (105, 966) and average number of amplicons detected were 15.3 per primer. Out of the 321 amplicons amplified, 301 were polymorphic showing 93.77% polymorphism with average of 14.3 per primer. Among the studied species, high genetic diversity was observed in A. manihot subsp. tetraphyllus var. tetraphyllus (0.1711), whereas lowest genetic diversity was observed in A. manihot subsp. tetraphyllus var. pungens. Among the studied species highest (0.9095) similarity index was observed between A. esculentus and A. caillei whereas A. palianus and A. crinitus exhibited lowest (0.5149) similarity index. The UPGMA based cluster analysis clearly distinguishes the Abelmoschus species into three major clusters – I, II and III. This study validate the utility of RAPD markers as a reliable tool for phylogenetic relationships as well as effective characterization of Abelmoschus genetic resources.